Non-IFRS Applications: Financial Reporting Accuracy and Transparency challenges - Guo, Ziang (International Journal of Global Economics and Management, 2024)
In a globalized economy, many companies are increasingly adopting non-IFRS to enhance their financial disclosure and provide shareholders with a clearer view of business performance. The phenomenon has sparked a deep debate in academic circles about transparency and accuracy in financial reporting. In this way, this paper can further explore the application of non-IFRS in accounting records and its impact on the precision and clarity of financial disclosure. Through cross-industry empirical case studies and a careful review of the existing literature, we explore the motivations for adopting such unconventional accounting parameters, and identify potential comparative difficulties and normalization differences that may lead to loss of equivalence. The findings reveal that while non-IFRS can contribute to enhancing information content and enhancing insights into corporate management effectiveness, they can also mislead investors. In view of this, our research advocates promoting the harmonization of non-IFRS to enhance the quality of accounting reporting, and calls on regulators to strengthen the policy framework to further safeguard the interests of multiple stakeholders, including investors.